2009
DOI: 10.1111/j.1547-5069.2009.01286.x
|View full text |Cite
|
Sign up to set email alerts
|

Defining Clinical Assessment Standards for Bachelor's‐Prepared Nurses in Switzerland

Abstract: Clinical assessment education that teaches a systematic approach to data collection, analysis, and reporting is central to producing excellent clinical professionals.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 5 publications
0
6
0
1
Order By: Relevance
“…I EU's Tuningprosjekt er målet å definere sykepleiekompetanse. Her framkommer det at sykepleiere skal kunne gjøre omfattende og systematiske undersøkelser av pasienten (17). Mangelen på funn av skandinavisk forskningslitteratur om emnet kan skyldes at SKUV ikke er innført i sykepleierutdanningene i disse landene.…”
Section: Premisser For Praksisunclassified
“…I EU's Tuningprosjekt er målet å definere sykepleiekompetanse. Her framkommer det at sykepleiere skal kunne gjøre omfattende og systematiske undersøkelser av pasienten (17). Mangelen på funn av skandinavisk forskningslitteratur om emnet kan skyldes at SKUV ikke er innført i sykepleierutdanningene i disse landene.…”
Section: Premisser For Praksisunclassified
“…In Switzerland, at the start of the 2000s, when nursing studies began to be taught in Universities of Applied Sciences, training programs were re-evaluated, and teaching about clinical evaluation was reinforced and deepened (Lindpaintner et al, 2009). Respondents Finally, our results showed that nurse clinicians and nurse specialists were more likely to report performing physical assessments once per week or less, and less likely to report performing them daily than other participants in our survey.…”
Section: Discussionmentioning
confidence: 74%
“…Another hypothetical explanation is that more experienced nurses, the majority of whom had not undergone a university-level nursing education, have had less extensive training in nursing physical assessment. Indeed, physical assessments were long considered the prerogative of physicians and were not systematically taught to nurses (Lindpaintner et al, 2009).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All learners must achieve mastery learning, namely mastering basic competencies. The pace of learners is not the same, and the assessment uses criterion references (Lindpaintner, Bischofberger, Brenner, & Knuppel, 2009) [12].…”
Section: B Nurses Competencementioning
confidence: 99%